High Prevalence of Intra-Familial Co-colonization by Extended-Spectrum Cephalosporin Resistant Enterobacteriaceae in Preschool Children and Their Parents in Dutch Households - Liakopoulos, Apostolos; van den Bunt, Gerrita; Geurts, Yvon; Bootsma, Martin C. J.; Toleman, Mark; Ceccarelli, Daniela; van Pelt, Wilfrid; Mevius, Dik J. (Frontiers in Microbiology, 2018)
Extended-spectrum cephalosporin-resistant (ESCR) Enterobacteriaceae pose a serious infection control challenge for public health. The emergence of the ESCR phenotype is mostly facilitated by plasmid-mediated horizontal ESBL and AmpC gene transfer within Enterobacteriaceae. Current data regarding the plasmid contribution to this emergence within the Dutch human population is limited. Hence, the aim of this study was to gain insight into the role of plasmids in the dissemination of ESBL/AmpC genes inside Dutch households with preschool children and precisely delineate co-colonization. In 87 ESCR Enterobacteriaceae from faecal samples of parents and preschool children within 66 Dutch households, genomic localization, plasmid type and insertion sequences linked to ESBL/AmpC genes were determined. Chromosomal location of ESBL/AmpC genes was confirmed when needed. An epidemiologically relevant subset of the isolates based on household co-carriage, was assessed by Multilocus Sequence Typing and Pulsed-Field Gel Electrophoresis for genetic relatedness. The narrow-host range I1α and F plasmids were the major facilitators of ESBL/AmpC-gene dissemination. Interestingly, we documented a relatively high occurrence of chromosomal integration of typically plasmid-encoded ESBL/AmpC-genes. A high diversity of non-epidemic Escherichia coli sequence types (STs) was revealed; the predominant STs belonged to the pandemic lineages of extraintestinal pathogenic E. coli ST131 and ST69. Intra-familiar co-carriage by identical ESCR Enterobacteriaceae was documented in 7 households compared to 14 based on sole gene typing as previously reported. Co-carriage was more frequent than expected based on pure chance, suggesting clonal transmission between children and parents within the household.